Dynamic Optimization of Arbitrary 2D Structures Using Ground Structure Method with High-Order Composite Implicit Time Integration - วางขุนทด, พฤกษา; Su, Rut; ตั้งอร่ามวงศ์, เสวกชัย (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
This paper presents an implementation for ground structure based topology optimization of arbitrary 2D structures subjected to dynamic load. Topology optimization of the structure is achieved by employing the Bi-directional Evolutionary Structural Optimization (BESO) algorithm, which aims to reduce the structural weight by using strain energy as the basis for the removal and addition of elements. To solve the structural dynamic problem, a high-order composite implicit time integration scheme is employed, utilizing the same effective stiffness matrix across all sub-steps to reduce computational costs. The effectiveness of the proposed method is validated through numerical examples.